Role Conflict of Spiritual and Moral Values in Education, Specifically in the Context of Malaviya's Philosophy and the National Education Policy (NEP) 2020 - SINGH, SHRIKANT (International Journal of Religion Education and Law, 2026)
This research examines the inclusion within educational contexts in Kanpur, Uttar Pradesh of spiritual as well as moral values through the study of 81 participants from government, private and non-profit schools. The main toss were to examine the efficacy of values integration in the curriculum and to identify the conflict which emerge from implication of these values to a largely secular domain of  Indian education system. Two hypotheses guided the research: First, spiritual and moral values integration in education improves educational outcomes, and second, confrontation of secular practices with spiritual values impairs educational work of values education. A mixed methods research design was employed in which a structured survey was used to collect quantitative data and in depth interviews were used to gain empirical insight. Analysis of results indicates that out of 75 percent, 75 percent of the respondents believe that values are well integrated into their curriculum and there is a significant positive correlation (r = 0.65, p 0.01) between values integration and academic performance. Nevertheless, 60% of participants indicated that secular educational practises clashed with the insertion of these values and reported that this clashed with students’ ethical development (β = -0.52, p 0.05). The discussion explains the importance of sounding a cautionary note and a counter attracting cure of moralizing education not to the exclusion of academic rigor, but the other way around. The paper emphasizes the importance of resolving conflicts indicated among the identified ones for improving the effectiveness of values education overall. Lastly, if we truly want to create an educational environment that includes spiritual and moral values along with academic attainment in order to truly prepare our students to be responsible and ethical members of society, this has to be a reality. To achieve this goal, the study suggests such recommendations as imposed on curriculum development, teacher training, and community engagement to leverage such systemic changes that would consolidate effective integration of values in education. This research adds to the ongoing discussion about values and their place in education, specifically, ways in which the same values can lead to different outcomes for different students in holistic development